The strategic use of nudging and behavioural approaches in public health policy during the coronavirus crisis - Gabriela Michalek; Reimund Schwarze (Helmholtz-Zentrum für Umweltforschung (UFZ), 2020)
Nudging and behavioural insights need to be taken into account in strategic action planning for suppression and reduction of pandemic effects. This paper focuses on a few selected areas of significant importance to getting SAR-CoV2 under control in both the nonpharmaceutical and the pharmaceutical phase, i.e. after the development of an effective vaccine.
Keywords: 330; Coronavirus; Coping-Strategie; Impfung; Gesundheitsvorsorge; Deutschland